Evolution of E-commerce and Global Marketing - Cécile Ferrera; Eowyne Kessedjian (International Journal of Technology for Business (IJTB), 2019)
The development of new technologies in the last few years turned internet into a commercial medium that has transformed businesses all over the world. Indeed, we can be connected to internet from anywhere and anytime we want, with just one click. This evolution made the world interconnected and has permitted the development of e-commerce. More and more people communicate with internet because they are finding it easier and marketing strategies are being adapted to these changes. This article discusses the evolution of global marketing and e-commerce in order to understand what has changed in such a short time and what are the consequent impact of this new form of commerce.
Keywords: 650; Global Marketing; E-Commerce; Data Protection; Social Impact; Consumer Behaviour